La "caja común" como modelo de gestión operativo financiero en la compañía de transporte San Francisco de Chillogallo S.A. - Sánchez Angulo, Gabriela Elizabeth (2012)
The San Francisco company Chillogallo S.A. with over 50 years offering service south of Quito not escape this reality and in order to strengthen its business structure, it has been proposed to comply with the law and apply the model of common box in the organization. For this purpose the creation of four areas that will provide support to the system and enable the proper implementation of the management model is needed. The operational area is responsible for the programming of the fleet looking for customer satisfaction. The maintenance ensure the effective productivity of each unit and its operation in the operation.